Overcoming obstacles to integrate of Media Education in school curricula - Tomé, V.; Helena Menezes (Asian Conference on Education 2009: Local Problems, Global Solutions, 2009)
The production of media messages contributes to the development of critical skills on the analyses of media messages. However, teachers and students do not have opportunities to work in the production of media messages at school. This paper presents the preliminary results of a research project whose aim is to help teachers and students in the production of on-line and/or printed school newspapers in order to develop Media Education in the Region of Castelo Branco, Portugal.